PERAN DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KOTA PEKANBARU DALAM PENGELOLAAN SAMPAH DI KECAMATAN TAMPAN TAHUN 2016 - Eko Prasetya; M. Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
As a residential area, it turns out that Tampan District has a significant potential for waste production. The amount of potential waste generated in Tampan District requires special treatment so that the negative effects of accumulating unloaded waste can be avoided. But found in the field in several places in the District of Tampan, namely on Jl. Stork Sakti, Jl. Garuda Sakti, Jl. S.M Amin, Jl. Pekanbaru-Bangkinang, Jl. Cipta Karya Gg Keluarga, Arengka Morning Market, Tuesday Panam Market, there are still piles of garbage that have not been transported for days. The formulation of the problem in this study is, what is the role of the Pekanbaru City Environment and Cleanliness Office in waste management in Tampan District in 2016? What are the inhibiting factors of the Pekanbaru City Environment and Cleanliness Office in waste management in Tampan District in 2016? The purpose of the study was to determine the role of the Pekanbaru City Environment and Sanitation Department in waste management in Tampan District in 2016, to determine the inhibiting factors of the Pekanbaru City Environment and Cleanliness Office in waste management in the Tampan District 2016. The primary data source was through interviews and secondary data source. The data analysis technique was carried out with a qualitative descriptive analysis. The cause of the accumulation of garbage in the city of Pekanbaru, especially in the area of the District of Tampan is the inability of PT. MIG as a partner of the Pekanbaru City Environment and Sanitation Office transports waste, causing a pile of garbage in several places. And the rubbish that is discarded by the community that is not on schedule creates a buildup that must be carried by officers in the next schedule. Waste sorting has not yet been fully carried out by the people of the Tampan District of Pekanbaru City, and the demand for garbage storage facilities in Pekanbaru City is not fulfilled, including in the Tampan District area. Tampan District as an area with a large amount of housing apparently has no TPS as a temporary garbage collection place for the community. Obstacles to contracts with partners, lack of socialization, vehicles and equipment, limited budgeting, and community response. Keywords: Role, Waste Management